Radiobiological effects of tritiated water short-term exposure on V79 clonogenic cell survival. (1st February 2018) - Siragusa, Mattia; Fredericia, Pil M.; Jensen, Mikael; Groesser, Torsten
Abstract: Purpose: We set out to improve the accuracy of absorbed dose calculations for in vitro measurements of the relative biological effectiveness (RBE) of tritiated water (HTO) for the clonogenic cell survival assay, also considering the influence of the end-of-track linear energy transfer (LET) of low-energy electrons. Materials and methods: The COmputation Of Local Electron Release (COOLER) program was adopted to investigate the cell geometry and the tritium full beta-decay spectrum impact on the S-values and subsequently on the RBE of HTO for clonogenic cell survival at similar high dose rates (HDR). Results: S-values for cells growing in suspension are usually comparable to those for adherent cells. RBEs calculated at the 10% survival fraction through the use of the average energy are almost similar to those obtained with the beta-spectrum. For adherent cells, an RBE of 1.6 was found when HTO cell survival curves were compared to acute γ-ray exposures. Irrespective of the geometrical configuration, the RBE was 2.0 when the comparison was made with similar dose rates. Conclusions: These results underline the importance of irradiating at equal dose rates and cell culture conditions when measuring in vitro RBE-values.